Preliminary studies of 12S-8P and 12S-14P Hybrid-Excited Flux Switching Machine with FEC in radial direction by using JMAG-designer software - Rahimi, S. Khalidah; Ahmad, Md. Zarafi; Sulaiman, Erwan; Othman, Syed M. Naufal Syed; Soomro, Hassan Ali (International Journal of Engineering and Technology, 2018)
In this paper, design analysis of Hybrid- Excited Flux Switching Machine (H-EFSM) with 12Slot-8Pole (12S-8P) and 12Slot-14Pole (12S-14P) topologies are presented. H-EFSM  has  been introduced in which  the advantage  of  Permanent  Magnet  (PM)  machines  and  DC  Field Excitation Coil (FEC) synchronous machines is combined. H-EFSM  design proposed less permanent magnet consumption, high to torque/power density and high efficiency. In recent, most of H-EFSM having FEC arranged  in  theta  direction  that affect in flux production which cause less flux generation and machines performances.  Therefore, a design of 12S-8P and 12S-14P H-EFSM with FEC arranged in radial direction is proposed to prevent flux cancellation and produce high flux linkage. Performance analysis of 12S-8P and 12S-14 H-EFSM such as PM flux, induced voltage, cogging torque and flux distribution are investigated by 2-D Finite Element Analysis (2D-FEA). A design with 12S-14P configuration has achieved the higher torque and power with 220.15Nm and  92.45kW, respectively at maximum field and armature current density